2023
DOI: 10.3389/fnut.2023.1187672
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and prognostic value of malnutrition in patients with acute coronary syndrome and chronic kidney disease

Abstract: BackgroundMalnutrition is a rising global health issue associated with unfavorable outcomes of a variety of disorders. Currently, the prevalence and prognostic significance of malnutrition to patients with acute coronary syndrome (ACS) and chronic kidney disease (CKD) remained largely unclear.MethodsA total of 705 patients diagnosed with ACS and CKD in the First Affiliated Hospital of Wenzhou Medical University between 2013 and 2021 were included in this retrospective cohort study. Malnutrition was assessed by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 56 publications
1
4
0
Order By: Relevance
“…Ni et al discovered that a lower PNI was independently associated with an increased risk of mortality and enhanced the predictive capability of the GRACE score for overall death and MACEs in patients with ACS and CKD. Similar findings were observed with CONUT and PNI ( 89 ). Thus, enhancing the pre-angiography nutritional status of patients with CKD based on the PNI value can reduce the incidence of CA-AKI.…”
Section: Available Nutritional Assessment Methods For Patients With C...supporting
confidence: 89%
See 1 more Smart Citation
“…Ni et al discovered that a lower PNI was independently associated with an increased risk of mortality and enhanced the predictive capability of the GRACE score for overall death and MACEs in patients with ACS and CKD. Similar findings were observed with CONUT and PNI ( 89 ). Thus, enhancing the pre-angiography nutritional status of patients with CKD based on the PNI value can reduce the incidence of CA-AKI.…”
Section: Available Nutritional Assessment Methods For Patients With C...supporting
confidence: 89%
“…In recent years, the relevance of the CONUT score in CKD has attracted significant attention. As mentioned above, similar to PNI, the CONUT score enhanced the predictive ability of the GRACE score for overall death and MACEs in patients with ACS and CKD ( 89 ). In addition, the CONUT score exhibited an independent relationship with prior CVD in patients with CKD and demonstrated a superior correlation with disease activity in patients with lupus nephritis compared with other nutritional evaluation indexes ( 84 , 85 ).…”
Section: Available Nutritional Assessment Methods For Patients With C...mentioning
confidence: 90%
“…Nutritional status influences the body’s inflammatory response, and consistent nutritional management is crucial for patients with critical illness to recover from inflammatory injury [ 27 , 29 ]. Although the prevalence of malnutrition exhibited significant discrepancies, its association with poorer outcomes remains clear and sound [ 19 22 , 30 , 31 ]. However, the importance of screening and monitoring for malnutrition in patients with ACS hasn’t drawn enough concern from clinical guidelines and practice [ 32 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…In another cohort with 705 patients diagnosed with ACS and chronic kidney disease (CKD), malnutrition was found in 30%, 80%, and 90% of the population according to the PNI, CONUT, and GNRI, respectively 26 . Data from 5,062 ACS patients suggested that malnutrition prevailed in over 50% of cases based on the CONUT score, NRI, or PNI 27 .…”
Section: Komici Et Al Evaluated the Nutritional Status Of 174 Elderly...mentioning
confidence: 99%
“…Although the prevalence of malnutrition exhibited significant discrepancies, its association with poorer outcomes remains clear and sound [23][24][25][26][27][28] . However, the importance of screening and monitoring for malnutrition in patients with ACS hasn't drawn enough concern from clinical guidelines and practice 13,14 .…”
Section: Komici Et Al Evaluated the Nutritional Status Of 174 Elderly...mentioning
confidence: 99%